Histologic type predicts disparate outcomes in pediatric hepatocellular neoplasms: A Pediatric Surgical Oncology Research Collaborative study. Issue 14 (13th May 2022) - Short, Scott S.; Kastenberg, Zachary J.; Wei, Guo; Bondoc, Alex; Dasgupta, Roshni; Tiao, Greg M.; Watters, Erin; Heaton, Todd E.; Lotakis, Dimitra; La Quaglia, Michael P.; Murphy, Andrew J.; Davidoff, Andrew M.; et al.
Abstract : Background: Hepatocellular carcinoma (HCC) is a rare cancer in children, with various histologic subtypes and a paucity of data to guide clinical management and predict prognosis. Methods: A multi‐institutional review of children with hepatocellular neoplasms was performed, including demographic, staging, treatment, and outcomes data. Patients were categorized as having conventional HCC (cHCC) with or without underlying liver disease, fibrolamellar carcinoma (FLC), and hepatoblastoma with HCC features (HB‐HCC). Univariate and multivariate analyses identified predictors of mortality and relapse. RESULTS: In total, 262 children were identified; and an institutional histologic review revealed 110 cHCCs (42%; 69 normal background liver, 34 inflammatory/cirrhotic, 7 unknown), 119 FLCs (45%), and 33 HB‐HCCs (12%). The authors observed notable differences in presentation and behavior among tumor subtypes, including increased lymph node involvement in FLC and higher stage in cHCC. Factors associated with mortality included cHCC (hazard ratio [HR], 1.63; P = .038), elevated α‐fetoprotein (HR, 3.1; P = .014), multifocality (HR, 2.4; P < .001), and PRETEXT (pretreatment extent of disease) stage IV (HR, 5.76; P < .001). Multivariate analysis identified increased mortality in cHCC versus FLC (HR, 2.2; P = .004) and in unresectable tumors (HR, 3.4; P < .001). Disease‐free status at any point predicted survival. Conclusions: This multi‐institutional, detailed data set allowed a comprehensive analysis of outcomes for children with these rare hepatocellular neoplasms. The current data demonstrated that pediatric HCC subtypes are not equivalent entities because FLC and cHCC have distinct anatomic patterns and outcomes in concert with their known molecular differences. This data set will be further used to elucidate the impact of histology on specific treatment responses, with the goal of designing risk‐stratified algorithms for children with HCC. Lay Summary: This is the largest reported granular data set on children with hepatocellular carcinoma. The study evaluates different subtypes of hepatocellular carcinoma and identifies key differences between subtypes. This information is pivotal in improving understanding of these rare cancers and may be used to improve clinical management and subsequent outcome in children with these rare malignancies. Abstract : Data from this study demonstrated that pediatric hepatocellular carcinoma subtypes are not equivalent entities. This data set of more than 250 children with hepatocellular carcinoma may be used to guide treatment and impact outcomes in children.